Effect of Plasma Nitrocaburizing on the Mechanical and Corrosion Properties of SS 304 - Aris Widyo Nugroho, Harun Nur Rosyid, Tjipto Sujitno (Trans Tech Publications, Switzerland, 2015)
In this study, the mechanical properties and corrosion properties of plasma nitrocarburized 304 stainless steel at various processing times was investigated. Plasma nitrocarburizing was carried out at different processing time durations which varied from 60 min to 300 min at fixed temperature of 500 Â°C in an atmosphere of 78 vol.% N2, 19 vol.% H2 and 3 vol.% CH4. An Optical microscope and SEM coupled with EDS have been used to characterize the microstructural and the elemental depth profiles in which the thickness of the modified layers is derived. Microindentation method is used for the study of mechanical performance of the nitrocarburized material. Corrosion properties were investigated using potentiostat method in a 1 wt% NaCl solution. The result shows that the microhardness increases to a maximum value of more than two times compared to that of the untreated one. The corrosion performance was found being treatment time duration dependent.